Investigations on the interactions between the endophyte nitrogen fixing bacterium Gluconacetobacter diazotrophicus and tomato plants - Franchini, Martina (2021)
The need to find new and more sustainable agricultural practices is a pressing matter of our times. The development and employment of microbial-based biofertilisers is one of the solutions advanced by science to reduce the amount of chemicals that are released in the environment to sustain high yield agricultural production. Gluconacetobacter diazotrophicus (Gd) is a non-nodulating endophytic nitrogen-fixing bacterium, first isolated from sugarcane plants. It has been shown to be capable of colonising a wide range of crops and provide beneficial effects to the host plant thanks to both phytohormones production and nitrogen fixation. The aim of this project was to investigate the effects elicited on tomato plants by the Gd strain AZ0019 and to elucidate the molecular mechanisms that lie behind Gd positive effect on plants health and yield. Firstly, the achievement of a consistent microbial inoculation protocol for tomato plants was addressed in order to obtain a repeatable set up that would also allow molecular analyses on treated plants. In-soil colonisation experiments were initially tested with a promising outcome, showing improved growth in the wild type (WT) strain treated plants. However, the results scarce consistency, along with the high number of variables in this type of growth systems, led to the prioritisation of a more controllable setup. Bacterial inoculation on plants grown on MS agar or rockwool substrates was subsequently investigated, but low repeatability and inadequate colonisation success, in particular on the Money Maker tomato variety, discouraged further testing with this strategy. These attempts led to the development of a hydroponic system setup, in which the application of Gd through root dipping induced a consistent and repeatable growth promotion effect. With the employment of the above-mentioned hydroponic setup, investigations on the effects of Gd on tomato plants, both from a phenotypical and a molecular point of view, were addressed. More specifically, the response induced by the inoculation of the WT Gd strain was compared to the one elicited by a N-fixation impaired mutant strain of Gd, nifD-. The nifD- strain showed to be promoting the plants growth to some extent, even though a stronger beneficial effect was obtained after the inoculation of the WT strain. This comparison provided insight on the relevance of N-fixation contribution to the general plant growth promoting (PGP) effect provided by Gd to the host plant. Moreover, thanks to the employment of GUS and GFP tagged bacterial strains and the setup of a consistent protocol for the quantification of the bacterial colonisation, Gd localisation in the root system and colonisation rate could be monitored. Gd was found to be mainly localised on the root surface and in the root intercellular spaces, however it also observed in correspondence of lateral roots emergence sites and adhering to root hairs. In some cases, indication of intracellular colonisation was detected. Particular interest was posed on the molecular response of tomato plants to the interaction with Gd. A transcriptomic analysis was carried out on Gd-inoculated tomato roots in comparison to uninoculated plants, so to assess the plants molecular response to the interaction with either of the two Gd strains tested (WT or nifD-) at different nitrogen levels in the growth substrate, at 1- and 14-days post bacterial inoculation (dpi).